Smart-Valleys toolkit: An e-learning tool for the sustainable use of inland valleys for agricultural development and biodiversity and ecosystem services preservation - Dossou-Yovo, Elliott Ronald; Futakuchi, Kiochi (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Increased reliance on fertilizers and pesticides in rice production has proven unsustainable and ineffective due to soil depletion and pesticide-induced pest outbreaks, rising fertilizer costs, and the negative effects of pesticide and fertilizer use on human health and the environment. The integrated rice-fish system offers a large range of environmental, economic, and social benefits by improving diversification, intensification, profitability, and sustainability through the complementary utilization of land and water uses. It also ensures an appropriate supply of carbon, animal protein, minerals, and vitamins, contributing to food and nutrition security. However, due to socioeconomic, environmental, technological, and institutional constraints, the integrated rice-fish system remains marginal in Mali, as in most African countries. A first draft of the integrated rice–fish toolkit was produced by AfricaRice and WorldFish team to strengthen the capacity of and facilitate adoption by the stakeholders. A workshop has been organized on June 21 to validate the toolkit before finalization by the end of July.